Bearing capacity optimization of T-shaped soil-cement column-improved soft ground under soft fill - Ni, Pengpeng (2022)
During dredging activities, a large amount of dredged clay slurry or lump is produced. A dumping site composed of soft clay near the water body is often used to deposit dredged soft fill. Soil-cement columns are commonly employed to treat the soft ground for this application. Under soft fill, failure of soft clay dominates the behaviour of composite ground. Hence, a soil-cement slab is needed to form a load transfer platform above the columns, which is costly. As an alternative, the use of T-shaped column with an enlarged column cap is proposed. In this study, the responses of composite ground with T-shaped column are measured experimentally, which are used to calibrate a numerical model. The results of numerical parametric analyses show that the implementation of T-shaped column under soft fill can change the governing failure mode into column failure, once the diameter of column cap exceeds a certain value, after which the improvement efficiency is the same between T-shaped column and column-slab system. The height of column cap results in negligible difference in bearing capacity, and a minimum value of 0.3 m is suggested for use in design to avoid punching failure.